2011
DOI: 10.1111/j.1365-2214.2011.01277.x
|View full text |Cite
|
Sign up to set email alerts
|

An examination of information‐processing skills among inhalant‐using adolescents

Abstract: Inhalant users begin abusing substances at a younger age and suffer from more verbal and non-verbal processing, behavioural, language and memory problems than non-inhalant users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Alcohol and psychoactive substances requiring control were reduced to alcohol use: 19 categorical variable based on frequency of use by a MACS-derived algorithm; cigarette smoking: 20 MACS-derived algorithm generating total pack-years; and cannabis 21 and nitrite inhalant (“popper”) use frequencies 22 (none vs. any use) [all by self-report]. Psychotropic medication use 23 was controlled by use at assessment derived from self-report based upon relevant drugs listed across psychotropic categories.…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol and psychoactive substances requiring control were reduced to alcohol use: 19 categorical variable based on frequency of use by a MACS-derived algorithm; cigarette smoking: 20 MACS-derived algorithm generating total pack-years; and cannabis 21 and nitrite inhalant (“popper”) use frequencies 22 (none vs. any use) [all by self-report]. Psychotropic medication use 23 was controlled by use at assessment derived from self-report based upon relevant drugs listed across psychotropic categories.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is interesting to note that Takagi and collaborators [see (11,12)] have reported that inhalant users show, when compared with consumers of other drugs and controls, the worst performance in tasks that measure attention, memory, cognitive control, and processing speed. In line with this, (13,14) have also described more significant deficits in working memory, processing speed, concept formation, and mental flexibility in adolescents that have used several drugs, including inhalants, compared to adolescents with no inhalants in their consumption history.…”
Section: Introductionmentioning
confidence: 68%
“…We must point out that the neuropsychological exploration performed here was focused on only four measures of executive functioning based on previous reports of these measures being affected in inhalant users (14,39). It is possible that the detected decreased efficiency in the DMN, FPN, and SN may be responsible for other cognitive alterations and mental health problems also described among inhalant-abusing adolescents (62), which were not assessed in our research subjects.…”
Section: Discussionmentioning
confidence: 98%
“…Scott and Scott () recruited 461 adolescents from the Southwest Texas Juvenile Detention Center (JDC) to research information processing differences between 158 PSI and 303 PSO users. The findings of this first research indicated that PSI participants scored significantly worse on processing speed and working memory in comparison to the 303 PSO users.…”
Section: Methodsmentioning
confidence: 99%
“…Other inhalant researchers did not address the interactions of psychosocial functioning or drug use severity nor the effect of processing speed upon ECF (Takagi et al . ; Scott & Scott ).…”
Section: Introductionmentioning
confidence: 99%